Revascularization Time Matters in Liver Transplantation: Prolonged Implantation of Marginal Grafts Independently Predicts Inferior Transplant Outcomes in the Short and Long Term. (July 2018) - Buchholz, Bettina M.; Gerlach, Undine A.; Chandrabalan, Vishnu V.; Hodson, James; Gunson, Bridget; Mergental, Hynek; Muiesan, Paolo; Isaac, John R; Roberts, Keith J.; Mirza, Darius F; Perera, M Thamara PR
Abstract : Background: In the era of marginal organ utilization, the impact of revascularization time (RT) on outcomes in liver transplantation (LT) has not been reported. Methods: All primary LT performed in Birmingham between 2009 and 2014 (n=678) with portal reperfusion first were stratified according to RT (<44 vs. ≥44 min) and graft quality (SLG, Donor risk index [DRI]<2.3 vs. MLG, DRI≥2.3). Results: Compared to RT<44, a significantly greater incidence of early allograft dysfunction (EAD) (29% vs. 47%, p=<0.001), post-transplant acute kidney injury (AKI) (39% vs. 60%, p=<0.001) and new-onset AKI after LT (37% vs. 56%, p=<0.001) occurred after RT≥44. RT≥44 was also associated with adverse long-term outcome (3-year graft survival 92% vs. 83%, p=0.001; 3-year patient survival 87% vs. 79%, p=0.004). RT≥44 independently predicted EAD, renal dysfunction and overall graft but not patient survival. The cumulative effect of prolonged revascularization in marginal grafts (MLG RT≥44 ) resulted in the worst transplant outcome compared to all other groups which could be mitigated by rapid revascularization (SLG RT<44, SLG RT≥44, MLG RT<44 vs. MLG RT≥44, EAD 24%, 39%, 39% vs. 69%, respectively; p=<0.001 and 3-year graft survival 94%, 87%, 88% vs. 70%, respectively; p=<0.001)(Figure 1 ). Conclusions: Prolonged graft revascularization places outcomes particularly of marginal liver grafts at risk, and this is a modifiable variable that relies on the expertise of the implanting surgeon and also has implications for transplant surgical training. Figure. No caption available.